PENGARUH NORMA SUBJEKTIF, PENGETAHUAN DAN EFIKASI DIRI TERHADAP KEPATUHAN ZAKAT PROFESI DI PEMERINTAH KOTA BENGKULU - Nining Pertiwi; Lismawati (JURNAL FAIRNESS, 2023)
The purpose of this research is to examine and analyze subjective norm, knowledge and self-efficacy on profession zakat compliance in Bengkulu City Government. The sample of this study is aimed at state civil servants who work in kindergartens, elementary schools and state junior high schools in Gading Cempaka District. This research was conducted by distributing questionnaires to 61 people, then the data were analyzed using multiple linear regression analysis. The results show that the variable subjective norm and knowledge have a positive effect, while self-efficacy has no positive effect on profession zakat compliance. Thus it can be concluded that what influences the compliance with zakat profession is knowledge and subjective norm